AFEBRILE PLASMODIUM KNOWLESI SEVERE MALARIA WITH A FATAL OUTCOME - Chang, Chee Yik (Journal of Ayub Medical College Abbottabad, 2023)
I read with great interest the article by Shah et al. on the causes of fever in adults in Thall and surrounding areas. Malaria was found to be the most common cause of fever in the study. However, clinicians need to be aware that not all malaria infection present with fever. I would like to share a fatal case of severe Plasmodium knowlesi malaria with no fever.